Weighted composition operators between spaces of Dirichlet type - Kumar, Sanjay (Revista Matemática Complutense, 2009)
In this work we characterize b oundedness and compactness of weighted comp osi tion op erators acting b etween Dirichlet typ e spaces by using Carleson measures. We also find essential norm estimates for these op erators.
Keywords: Bergman spaces; Carleson measure; essential norm; spaces of Dirichlet type; weighted compositon operators